Website Design as a Media for Marketing Marine Tourism Packages in Bali - Raihan Azhar Hanif; W. Pamungkas; DJ. Prihadi; AP. Dhahiyat; F. Kristiandhi (Jurnal Pariwisata Nusantara (JUWITA), 2025)
Purpose: To design a website as an effective marketing tool for marine tourism packages inBali, providing easy access for tourists to purchase packages and obtain information aboutdestinations.Method: This study employed the Waterfall method for website development, combiningprimary data (questionnaires distributed to 30 respondents) and secondary data (previousresearch, literature, and online sources). Analysis focused on website usability, content needs,and user interface design.Result: The website prototype was successfully developed using WordPress and includedfeatures such as package descriptions, booking options, customer testimonials, and interactiveelements. The System Usability Scale (SUS) results indicated a high usability score, supportingthe effectiveness of the design.Contribution: This research contributes to the tourism field by offering an innovative digitalsolution for marine tourism marketing. It facilitates easier access to information and bookingfor tourists while enhancing promotional efforts for tourism businesses in Bali. The websitemodel can serve as a reference for similar projects in other regions.